200k views
3 votes
(K² – 30k - 18 - 4K²) ÷ (3+k).​

1 Answer

4 votes

Answer:


k^2-30k-18-4k^2=(k+3)(-3k-21)+45

Explanation:

Given:


(k^2-30k-18-4k^2):(3+k)

Consider the expression
k^2-30k-18-4k^2. First, add the like term
k^2 and
-4k^2:


k^2-4k^2=-3k^2

Now, this expression is


-3k^2-30k-18

Divide
-3k^2-30k-18 by
k+3. Multiply
k+3 by
-3k and subtract the result from the
-3k^2-30k-18 to eliminate the highest term
-3k^2:


-3k^2-30k-18-(-3k)(k+3)=-3k^2-30k-18+3k^2+9k=-21k-18

Multiply
k+3 by -21 and subtract the result from
-21k-18:


-21k-18-(-21)(k+3)=-21k-18+21k+63=45

Hence,


k^2-30k-18-4k^2=(k+3)(-3k-21)+45

User Kyle Neary
by
6.4k points